A The Role of Green Marketing on the Purchase Intention of Uniqlo Brand Fast Fashion Products for Students at the State University of Jakarta: A Conceptual Framework - Fahyat, Dzaid Harris Putra Fahyat (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The fashion industry, ranked as the third-largest globally, faces significant environmental challenges, producing over 150 billion garments annually and generating substantial waste. This study explores the relationship between green marketing and purchase intention, focusing on Uniqlo’s fast fashion products among students at the State University of Jakarta. In this context, green marketing serves as the independent variable, while purchase intention functions as the dependent variable. It highlights the critical role of green marketing strategies in shaping consumer awareness and purchasing behavior towards environmentally friendly products. Through a comprehensive review of existing literature, the study constructs a conceptual framework that identifies key indicators influencing both green marketing and purchase intention. Findings suggest that effective green marketing not only enhances perceived product value but also fosters consumer loyalty and drives sustainable business practices. This research aims to fill gaps in current literature and provides actionable insights for companies to strengthen their marketing strategies, particularly in the context of influencer marketing.